2019
DOI: 10.1523/jneurosci.1779-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

PSA-NCAM Colocalized with Cholecystokinin-Expressing Cells in the Hippocampus Is Involved in Mediating Antidepressant Efficacy

Abstract: The extracellular glycan polysialic acid linked to neural cell adhesion molecule (PSA-NCAM) is principally expressed in the developing brain and the adult neurogenic regions. Although colocalization of PSA-NCAM with cholecystokinin (CCK) was found in the adult brain, the role of PSA-NCAM remains unclear. In this study, we aimed to elucidate the functional significance of PSA-NCAM in the CA1 region of the male mouse hippocampus. Combined fluorescence in situ hybridization and immunohistochemistry showed that fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
2
1
Order By: Relevance
“…Apparently contradicting our result, it has been reported that S100a10 knockout mice showed depressive-like symptoms 46 and S100a10 protein and mRNA in the cortex and hippocampus are known to increase after SSRI administration and decrease in both a mouse model of depression and depressive patients 40, [59][60][61][62] . On the other hand, S100a10 was significantly upregulated by chronic restraint stress in the lateral habenula 63 , the same as our result of DRN serotonin neurons.…”
Section: Discussioncontrasting
confidence: 99%
“…Apparently contradicting our result, it has been reported that S100a10 knockout mice showed depressive-like symptoms 46 and S100a10 protein and mRNA in the cortex and hippocampus are known to increase after SSRI administration and decrease in both a mouse model of depression and depressive patients 40, [59][60][61][62] . On the other hand, S100a10 was significantly upregulated by chronic restraint stress in the lateral habenula 63 , the same as our result of DRN serotonin neurons.…”
Section: Discussioncontrasting
confidence: 99%
“…These results were validated in some clinical studies. One clinical investigation has detected increased levels of NrCAM in the cerebrospinal fluid (CSF) of patients with unipolar depressive disorder (27). However, this was not in line with the findings from Hidese et al (20), which found NCAM was down-regulated in CSF of MDD compared with heathy controls (20).…”
Section: Discussionmentioning
confidence: 91%
“…The reasons for this discrepancy could be due to sample size, disease course, use of antidepressants, and protein determination techniques. Some studies have shown that the function of NrCAM depends on its glycosylation, in particular polysalification, known as polysialic acid (PSA) ( 28 ). There is growing evidence which support the importance of polysialylated NCAM (PSA-NCAM) in MDD ( 19 ).…”
Section: Discussionmentioning
confidence: 99%